ANALISIS ENERGI DAN ZAT GIZI MAKRO PADA MENU SARAPAN TERHADAP STATUS GIZI REMAJA DI SMP NEGERI 1 KABILA KABUPATEN BONE BOLANGO - Ruhmayanti, Nur Ayu; Yasin, Yade Kurnia (JOURNAL HEALTH AND NUTRITIONS, 2018)
ABSTRACT Based on the data, about 50% of adolescents (17 ? 20 years) do not get breakfast, 89% of adolescents believe that breakfast is somehow important and only 60% of them get breakfast regularly. Breakfast actually contributes for 15-30% of calorie fulfilment for daily need. There are only 26,1% of Indonesian children who consume drink (drinking water, tea or milk) and about 44,6% is less or do not get breakfast. Objective of research is to analyze energy intake and macro nutrients of breakfast menu and to identify correlation of energy intake and macro nutrients with nutritional status. Design of research is qualitative research with interview, questionnaire filling and recall of 24 hours methods at 171 respondents who are students of class VII at SMP Negeri 1 Kabila, District of Bone Bolango. Weight and height measurement are performed to determine respondents? nutritional status. The data are processed by SPSS program through non-parametric test as the data are not normally distributed. Finding: statistical data analysis shows that 88,9% of adolescents have less energy intake, 93% of adolescents have less carbohydrate intake, 53,2% of adolescents have less protein intake and 76% of adolescents have less fat intake from breakfast need. There is no significant correlation between energy intake and macro nutrients of breakfast menu with respondents? nutritional status as shown by value of significance for p > 0,05. Conclusion: Mostly adolescents at SMP Negeri 1 Kabila have less energy intake and macro nutrients of the need. There is no correlation between energy intake and breakfast nutrients with nutritional status of adolescents. Keywords: Breakfast, Adolescents, Macro Nutrients ABSTRAK Sekitar 50% remaja akhir (17-20 tahun) tidak sarapan, 89% remaja menyakini sarapan memang penting, namun yang sarapan secara teratur hanya 60%. Sarapan menyumbang 15-30% pemenuhan kalori dari kebutuhan sehari. Terdapat 26,1% anak Indonesia hanya mengonsumsi minuman (air putih, teh, atau susu) dan sekitar 44,6% kurang atau tidak sarapan. Tujuan penelitian untuk menganalisis asupan energi dan zat gizi makro menu sarapan dan mengidentifikasi hubungan asupan energi dan zat gizi makro dengan status gizi. Desain penelitian adalah analisis kualitatif dengan metode wawancara, pengisian kuesioner, dan recall 24 jam pada 171 responden yang merupakan siswa kelas VII SMP Negeri 1 Kabila Kabupaten Bone Bolango. Pengukuran berat badan dan tinggi badan dilakukan untuk menentukan status gizi responden. Data diolah dengan SPSS menggunakan uji non-parametrik karena data berdistribusi tidak normal. Hasil: Hasil data secara statistik menunjukkan 88,9% remaja memiliki asupan energi kurang, 93% remaja memiliki asupan karbohidrat kurang, 53,2% remaja dengan asupan protein kurang, dan 76% remaja dengan asupan lemak kurang dari kebutuhan sarapan. Tidak ditemukan hubungan signifikan antara asupan energi dan zat gizi makro dari menu sarapan dengan status gizi responden dengan nilai signifikansi p>0,05. Simpulan: Sebagian besar remaja di SMP Negeri 1 Kabila memiliki asupan energi dan zat gizi makro kurang dari kebutuhan. Tidak terdapat hubungan antara asupan energi dan zat gizi sarapan dengan status gizi remaja. Kata Kunci: sarapan, remaja, gizi makro